2005
DOI: 10.1002/eqe.530
|View full text |Cite
|
Sign up to set email alerts
|

Adapting earthquake actions in Eurocode 8 for performance-based seismic design

Abstract: SUMMARYPerformance-based seismic design (PBSD) can be considered as the coupling of expected levels of ground motion with desired levels of structural performance, with the objective of achieving greater control over earthquake-induced losses. Eurocode 8 (EC8) already envisages two design levels of motion, for no collapse and damage limitation performance targets, anchored to recommended return periods of 475 and 95 years, respectively. For PBSD the earthquake actions need to be presented in ways that are appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 22 publications
(20 reference statements)
3
32
0
Order By: Relevance
“…This will widen the plateau in order to encompass the localized peak. Bommer & Pinho [7] recently suggested that the control periods in Eurocode 8 may need to be lengthened to correctly specify…”
Section: Engineering Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This will widen the plateau in order to encompass the localized peak. Bommer & Pinho [7] recently suggested that the control periods in Eurocode 8 may need to be lengthened to correctly specify…”
Section: Engineering Implicationsmentioning
confidence: 99%
“…The importance of examining the shape of the displacement spectra proposed in design codes has recently been highlighted by Bommer & Pinho [7]. In a seismological context, a possible generation mechanism (fluids within the source) for these large-amplitude long-period motions is suggested based on previous observations of similar motions.…”
mentioning
confidence: 99%
“…Only the Eurocode 8 (type 2) response spectrum, anchored with the PGA475 values obtained in this study, reproduces the shape of the hazard-consistent response spectra reasonably well. This result gives an example of the known limitations of using a code spectral shape scaled with a single PGA value and the convenience of considering a spectral shape anchored at representative short-and longperiod spectral accelerations derived from PSHA estimates (e.g., Bommer and Pinho 2006), such as the 2003-NEHRP Provisions. More interestingly, this result shows that EC8 type 2 spectrum (intended for relatively stable regions) is more consistent with the UHS at the 475-year return period derived for the Region of Murcia than EC8 type 1 spectrum (intended for active regions).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, an over-or under-estimation of the first (as in Cartagena, see Figs. 6 and 7) and/or an unconstrained definition of the second may lead to unrealistic hazard-consistent response spectra (Pousse et al 2005;Bommer and Pinho 2006;Gaspar-Escribano and Benito 2007). This limitation is stronger in the NCSE-02 code, since the implementation of two spectral shapes in Eurocode 8 allows better constraint of the final spectrum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation